(untitled) (Research, Society and Development, 2021)
The aim of this study was to quantitatively and qualitatively evaluate peri-implant bone formation in maxillary sinus lift surgery without using biomaterial by means of tomographic and histological analysis. Patient attended the Latin American Institute of Dental Education and Research (ILAPEO) for rehabilitation of the posterior region of bilateral maxilla with low bone volume, sinus lift, and implant placements without biomaterial were performed. The postoperative follow-up was conducted through clinical and tomographic conditions, in the immediate postoperative, 3, 6, 9, and 36 months. During the postoperative period of 9 months, a local biopsy was performed with the aid of a 2 mm trephine to perform a histological analysis. It can be observed tomographically that the highest density found in the evaluated periods was 36 months (buccal 1766,5 and palatal 1716,75), that is, after application of functional load. Histological analysis showed that at 9 months the biopsy removed by trephine was composed of 52% of bone tissue and 48% of connective tissue, presenting a bone cytoarchitecture compatible with mature bone with few areas of immature bone. In conclusion, this technique, can be performed successfully, obtaining a gain of peri-implant bone volume with quality.